Study of the properties of gelatin and poly(vinyl alcohol) membranes for use as dressings (Research, Society and Development, 2022)
The skin is the largest organ of the human body and its main function is to protect the entire organism against the action of external agents. Due to the injuries caused to this organ and the technological advances in different areas, investigations have been increasingly frequent on polymeric membranes for use as dressings, bearing in mind that they must be non-toxic, have a high swelling capacity, soft consistency, which minimizes friction between fabric and membrane. A wide variety of hydrophilic polymers have been used in the preparation of membranes. In this work, the properties of membranes made from a high molecular weight polypeptide derived from the denaturation and structural degradation of animal collagen, gelatin (GE) type I, and the polymer produced through the polymerization of vinyl acetate followed by reaction of hydrolysis of poly(vinyl acetate), poly(vinyl alcohol) (PVA) with 80% degree of hydrolysis. The mixture of these materials in the preparation of membranes aims to obtain a material with excellent properties, because these, by themselves, already have good optical properties, hydrophilicity and good mechanical resistance, essential characteristics for use as dressings. For this purpose, pure GE and PVA membranes were produced by the casting method, as well as different compositions of 1/3, 1/4, 3/1 and 4/1 v/v GE/PVA, respectively. From the visual aspect, one can observe soft, flexible, translucent and colorless membranes in visible light with an average thickness of 27.01 μm, for application in superficial injuries in the dermis region, which has 70 to 120 μm in thickness.